Phosphorylation of Ezrin/Radixin/Moesin Proteins by LRRK2 Promotes the Rearrangement of Actin Cytoskeleton in Neuronal Morphogenesis - Parisiadou, Loukia (Society for Neuroscience, 2009)
Leucine-rich repeat kinase 2 (LRRK2) functions as a putative protein kinase of ezrin, radixin, and moesin (ERM) family proteins. A Parkinson's disease-related G2019S substitution in the kinase domain of LRRK2 further enhances the phosphorylation of ERM proteins. The phosphorylated ERM (pERM) proteins are restricted to the filopodia of growing neurites in which they tether filamentous actin (F-actin) to the cytoplasmic membrane and regulate the dynamics of filopodia protrusion. Here, we show that, in cultured neurons derived from LRRK2 G2019S transgenic mice, the number of pERM-positive and F-actin-enriched filopodia was significantly increased, and this correlates with the retardation of neurite outgrowth. Conversely, deletion of LRRK2, which lowered the pERM and F-actin contents in filopodia, promoted neurite outgrowth. Furthermore, inhibition of ERM phosphorylation or actin polymerization rescued the G2019S-dependent neuronal growth defects. These data support a model in which the G2019S mutation of LRRK2 causes a gain-of-function effect that perturbs the homeostasis of pERM and F-actin in sprouting neurites critical for neuronal morphogenesis.